Determination of Sun Protection Factor (SPF) in Areca catechu L. Fruit Fraction Lotion - Mustiqawati, Evi; Damayanti, Restu Harisma; Sarni, Sarni (Jurnal Promotif Preventif, 2025)
Areca catechu L. (betel nut) is known to contain bioactive compounds, particularly flavonoids and phenolics, which have potential antioxidant and photoprotective properties. These activities make it a promising natural ingredient for sunscreen formulations. This study aimed to determine the Sun Protection Factor (SPF) and evaluate the antioxidant activity of a lotion formulated with the Areca catechu L. fruit fraction. SPF was measured in vitro using a UV–Vis spectrophotometer, antioxidant activity was assessed using the DPPH method, and the physical stability of the lotion was evaluated. The results indicated that formulation F3 exhibited the highest SPF value of 24.82, categorized as ultra-protection. This formulation also demonstrated strong antioxidant activity, with an IC50 value of 5.075 mg/L. Phytochemical screening of the Areca catechu L. fraction confirmed the presence of phenolic and flavonoid compounds, supporting the observed photoprotective activity. Physical stability evaluation revealed that the Areca catechu L. fraction lotion maintained good stability and desirable physical characteristics throughout testing. These findings suggest that lotion formulated with Areca catechu L. fraction has strong potential as a natural sunscreen product, providing high-level protection and significant antioxidant activity, particularly in formulation F3.